2014
DOI: 10.1007/s11011-014-9483-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antipsychotic potential of aqueous fraction of Securinega virosa root bark extract in mice

Abstract: Securinega virosa (Roxb ex. Willd) Baill. is a plant which is commonly used in African traditional medicine in management of mental illness. Previous study showed that the crude methanolic root bark extract of the plant possesses antipsychotic activity. In this study, the antipsychotic potential of the residual aqueous fraction of the plant was evaluated using two experimental models, apomorphine induced stereotypic climbing behaviour and swim induced grooming, all in mice. The effect of the fraction on halope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…107 More recently, the extract of the same plant was evaluated on two murine experimental models, apomorphine-induced stereotypic climbing behavior and swim-induced The Securinega Alkaloids grooming. 108 The observed weak activity could be related to dopamine D1 or D2 receptors blockade. However, this fraction did not significantly potentiate haloperidol-induced catalepsy, a model for D2 blockade evaluation.…”
Section: Central Nervous System Propertiesmentioning
confidence: 99%
“…107 More recently, the extract of the same plant was evaluated on two murine experimental models, apomorphine-induced stereotypic climbing behavior and swim-induced The Securinega Alkaloids grooming. 108 The observed weak activity could be related to dopamine D1 or D2 receptors blockade. However, this fraction did not significantly potentiate haloperidol-induced catalepsy, a model for D2 blockade evaluation.…”
Section: Central Nervous System Propertiesmentioning
confidence: 99%
“…[1] Securinega alkaloids (SEAs) are a group of plant specialized metabolites with distinctive structural features and significant biological activities, such as antitumor, antibiotic, and central nervous system (CNS) stimulation. [2,3] Since the discovery of securinine (Figure 1), which is the first and representative member of this alkaloid group, over 100 SEAs have been isolated and characterized from species of genera Securinega and Flueggea (Euphorbiaceae). Feeding experiments have previously demonstrated that the tetracyclic scaffolds (rings A-D) of SEAs are assembled through multistep cascade reactions utilizing two amino acid precursors, l-lysine (ring A) and l-tyrosine (rings C and D), as general biosynthetic building blocks.…”
mentioning
confidence: 99%
“…The application of this strategy led to the efficient discovery and identification of three novel SEAs, suffranidines A-C (1-3, Figure 1), from F. suffruticosa. Structurally, compound 1 possessed an unprecedented 8/5/6/5/6/6/6/6-fused octacyclic architecture with a unique cage-shaped 3-azatricyclo[6.4.0.0 3,11 ]dodecane core. Compounds 2 and 3 are two highly modified SEA dimers containing additional C6 motifs.…”
mentioning
confidence: 99%
See 2 more Smart Citations